Ендокринні дизраптори та їх вплив на формування тиреоїдної патології у дітей - Маменко, М. Є. (Clinical Endocrinology and Endocrine Surgery, 2008)
The impact of the main goitergenes on the development of the non-toxic goiter in children in Eastern Ukraine is analyzed in the article. It deals with some results of the school-based 30-cluster survey of the prevalence of the goiter in children 6-11-y-old in Luhansk Region (WHO/ICCIDD/UNISEF, 2001, 2007). We've found out the mild level of iodine deficiency (the median of the urinary iodine concentration 83,0 μg/L) and moderate level of goiter prevalence (27,3%). The rate of goiter in urban clusters correlated with the level of atmosphere endocrine disruptors at the different parts of the big industrial cities. It was demonstrated that coexisting iodine deficiency and severe environmental conditions at the industrial cities can impair thyroid function in schoolchildren. The conclusion was made that normalization of iodine supplementation can improve thyroid function in children at the area with the multiple-factor goiter development.